ANALISIS MOTIVASI KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN MALINAU PROVINSI KALIMANTAN TIMUR - Sedarmayanti, Sedarmayanti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2013)
In an organization can not be separated from the human resources available, in addition to other resources. The achievement of an organization's vision, mission certainly not terlepasa of performance generated by existing employees.Therefore, in this case the district Regional Employment Board Malinau a formal organization in the District Government Malinau. Regional Employment Board Malinau certainly has the vision, mission and goals of the organization that must be understood by every employee. For fulfilling their visi, the mission must be supported with a strong work motivation of each employee. Starting from this, the thesis takes the title of "ANALYSIS OF MOTIVATION ON EMPLOYEES WORKING REGIONAL EMPLOYMENT AGENCY OF MALINAU PROVINCIAL EAST BORNEO". The purpose of this study was to determine the analyze of employee motivation at Regional Employment Board Malinau East Borneo Province. Apart from that, this study uses the concept of motivation from Victor Vroom is often known as expectancy theory (Expectancy Theory), in which the theory has major dimensions, namely: Expectancy, Instrumentality, and Valence. In terms of statistics, the motivation for this theory when stated in mathematical form is M = E x I x V, where the highest value is 1 and the lowest is -1. Based on this research, that each of the dimensions described in the description; 1. Expectancy, As has been stated that there are 6 items Expectancy dimensionalrepresentations, with the frequency of respondents' answers to the dimensions of expectancy is at 218 with a percentage score is 0.80 Thus, the dimension Expectancy respondents fall into the category of very high. 2. Instrumentality, For Instrumentality dimension statement contained 5 items, the frequency of respondents' answers to the dimensions Intrumentality total score is equal to 151.75, with a percentage score is 0.67. Thus, the responses to the dimensionsIntrumentalitas included in the high category. 3.Valence, Based on the total scores for the dimensions of Valence was the score at 76 with 0.35 percent Thus, the responses to the dimensions of value are included in the high category. Based on the analysis of the data for each dimension of the motivation variable, it is because this study refers to the theory of Victor Vroom where that motivation (M) = E x I x V, then M = 0.80 x 0.67 x 0.35 = 0.19 , if the results are interpreted in table interpretation, in the category of employee motivation enough. Where the dimensions of employee motivation are the highest and lowest Expectancy dimensions are the dimensions of Valence. Apart from that, quantitative data is supported by qualitative data in the form of interviews conducted by the researchers of the informants stated that employeemotivation Regional Employment Board Malinau generally far enough.